Differential Effects of Oxytocin on Visual Perspective Taking for Men and Women - Yue, Tong; Jiang, Yuhan; Yue, Caizhen; Huang, Xiting (Frontiers in Behavioral Neuroscience, 2017)
Although oxytocin (OXT) has been shown to lead to reduced self-orientation, no study to date has directly and effectively weakened the egocentric tendencies in perspective taking tasks for both men and women. In this double-blind, placebo-controlled, mixed design study we investigated the effects of OXT on men and women in visual perspective taking tasks. The results showed that OXT shortened the differences in response time between men and women in all experimental conditions. In addition, after OXT administration, the difference in reaction time between judging from one’s own perspective and judging from others’ perspectives decreased in female participants; however, this effect was not present in males. This may indicate that under OXT treatment, women have a higher tendency to overcome interference from their position and mindset when judging others’ perspectives. However, OXT did not affect participants’ accuracy, which is possibility because the used task was not suited to detect performance improvements caused by OXT. In summary, the above results may indicate that OXT could increase perspective-taking abilities through reducing self-bias and increasing the perception of others; furthermore, this trend mainly affected women rather than men.